NEW LABOR CODE TIME REQUIREMENT! - Bahronov Azizjon Fayzulloevich (Scholar Express Journals, 2023)
In this article, the Labor Code of the Republic of Uzbekistan and the newly revised Labor Code, the difference between the two, and the fact that the new Labor Code is the need of the hour are explained.
Keywords: Labor Code; labor relations; law; norms